2017
DOI: 10.1073/pnas.1711141115
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic control of pheromone MAPK signaling determines sexual fecundity in Candida albicans

Abstract: Several pathogenic species are capable of heritable and reversible switching between two epigenetic states, "white" and "opaque." In, white cells are essentially sterile, whereas opaque cells are mating-proficient. Here, we interrogate the mechanism by which the white-opaque switch regulates sexual fecundity and identify four genes in the pheromone MAPK pathway that are expressed at significantly higher levels in opaque cells than in white cells. These genes encode the β subunit of the G-protein complex (), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 63 publications
1
27
0
Order By: Relevance
“…Elevated pheromone response pathway activation and increased response to pheromones are critical to successful courtship during mating in S. cerevisiae and C. albicans [14, 15, 18]. S. cerevisiae utilizes the α-factor protease Bar1 and a -factor barrier Afb1 to discriminate mating partners with different pheromone levels and drive evolution towards higher pheromone production for efficient mating [4345].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Elevated pheromone response pathway activation and increased response to pheromones are critical to successful courtship during mating in S. cerevisiae and C. albicans [14, 15, 18]. S. cerevisiae utilizes the α-factor protease Bar1 and a -factor barrier Afb1 to discriminate mating partners with different pheromone levels and drive evolution towards higher pheromone production for efficient mating [4345].…”
Section: Resultsmentioning
confidence: 99%
“…Upregulation of the pheromone response pathway enhances mating efficiency; however, this upregulation can result in a fitness cost in S. cerevisiae and C. albicans [18, 48]. In yeast, a short-term experimental evolution experiment showed that mutations abrogating expression of 23 genes involved in mating conferred a fitness benefit during yeast growth when functions of these genes are not required [48].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The activities of Cek1 and Cek2 are regulated by Cpp1, a MAP kinase phosphatase [78]. Interestingly, STE4, CST5, CEK1, and CEK2 are expressed at lower levels in white cells than opaque cells [79], and their repression contributes to the sterility of white cells as white cells engineered to express STE4, CST5, and CEK2 (CEK1 was not tested) at levels similar to opaque cells have been shown to undergo mating at frequencies approaching that of opaque cells [79]. It is also interesting to note that Cek1 (rather than Cek2) appears to play a major role in opaque cell mating; opaque cek1 mutants mate at much lower frequencies than opaque cek2 mutants [78].…”
Section: Pheromone-signaling Pathway Controlmentioning
confidence: 99%